Comparison of PD-L1 tumor cell expression with 22C3, 28-8, and SP142 IHC assays across multiple tumor types - Jeffrey S Ross; Richard S P Huang; Jake G Maule; Lani K Clinton; Ryon P Graf; Jinpeng Xiao; Geoffrey R Oxnard (Journal for ImmunoTherapy of Cancer)
Background Multiple PD-L1 immunohistochemistry (IHC) assays, including DAKO 22C3, DAKO 28-8, and Ventana SP142 PD-L1 IHC assays, have been approved by the Food and Drug Administration as a companion diagnostic (CDx) for various antiprogrammed death-1 and antiprogrammed death ligand 1 (PD-L1) based cancer immunotherapies. Here we present 22C3, 28-8, and SP142 analysis of 418 tumor specimens encountered in routine clinical practice.Methods All specimens were tested with 22C3, 28-8, and SP142 assays following the manufacturer’s established staining protocols.Results The same PD-L1 status (defined as tumor cell expression (TC) scores with all three assays ≥1% or all <1%) was observed in 60.0% (251/418) tumor specimens (45.9% (192/418) were triple negative and 14.1% (59/418) were triple positive). A total of 54.1% (226/418) tumor cases were positive with at least one IHC assay (94.2% (213/226), 77.0% (174/226), and 28.8% (65/226) of these were positive for 22C3, 28-8 and SP142, respectively). Among the 40.0% (167/418) tumor cases that showed a different PD-L1 status, 62.3% (104/167) were 22C3+/28-8+/SP142−, and 28.7% (48/167) were 22C3+/28-8−/SP142−. The same PD-L1 status with all three antibody clones was observed in 48.7% (97/199) of NSCLC cases, and among these, 54.6% (53/97) were triple negative and 45.4% (44/97) triple positive. A total of 73.4% (146/199) NSCLC cases were positive with at least one IHC assay (95.2% (n=139/146), 82.2% (n=120/146), and 32.2% (n=47/146) were positive for 22C3, 28-8, and SP142, respectively). Among the 51.3% (102/199) NSCLC cases that showed a different status among the three IHC assays, 67.6% (69/102) were 22C3+/28-8+/SP142−, and 23.5% (24/102) were 22C3+/28-8−/SP142−. A total of 81.1% (43/53) lung squamous cell carcinoma, 72.1% (88/122) of lung adenocarcinoma, 69.6% (16/23) of non-small cell lung cancer (NSCLC) not otherwise specified (NOS), and 50.0% (4/8) of small cell lung carcinoma cases were positive with at least one IHC assay.Conclusions Our data suggest that 22C3 is the most sensitive PD-L1 IHC assay for tumor cell expression, followed by 28-8 and in turn by SP-142. These findings represent an additional factor for clinical teams to consider when deciding which PD-L1 IHC assay (and in turn which CDx-associated PD-L1 based immunotherapy) is most appropriate for each individual patient.